Characterization of Naphthaleneacetic Acid Binding to Receptor Sites on Cellular Membranes of Maize Coleoptile Tissue - Ray, Peter M. (1977)
Characteristics of and optimum conditions for saturable (“specific”) binding of [(14)C]naphthaleneacetic acid to sites located on membranous particles from maize (Zea mays L.) coleoptiles are described. Most, if not all, of the specific binding appears to be due to a single kinetic class of binding sites having a K(D) of 5 to 7 × 10(−7)m for naphthalene-1-acetic acid (NAA). Binding of NAA is insensitive to high monovalent salt concentrations, indicating that binding is not primarily ionic. However, specific binding is inhibited by Mg(2+) or Ca(2+) above 5 mm. Specific binding is improved by organic acids, especially citrate. Binding is heat-labile and is sensitive to agents that act either on proteins or on lipids. Specific binding is reversibly inactivated by reducing agents such as dithioerythritol; a reducible group, possibly a disulfide group, may be located at the binding site and required for its function. The affinity of the specific binding sites for auxins is modified by an unidentified dialyzable, heat-stable, apparently amphoteric, organic factor (“supernatant factor”) found in maize tissue.